Demand for wheat commodity in Algeria is a standard analytical study "for the period (1990- 2015". - عدالة, العجال (جامعة المسيلة, 2018)
The study examined the current and future demend of wheat, by analysing the affected factor on wheat in Alegria during 1990-2015 , that aims to analyse the couse of wheat growing amounts from a period to another, which led to a vast gap between the production and the consumption, that is importation of wheat affected the Algerian resources of foreign currency ,therefore , the Algerian government took serious reparations in agricurture .depending on the integration of several methods, like: national plan for agriculture development 2000-2004, as wellas , agriculture renewal policy 2008-2014, The studay adopted the descriptive method in the applied aspect ,and the inductive method in drawing conclusion , this last indicated the existence of a statistical singnificant positive relationship between the price of wheat and the quantity demanded of wheat , also,the existence of a statistically significant positive relationship between the income and the quantity demanded of wheat , most importantly , this studay called the farmers to work on soil producing wheat to increase an efficiency economic resources.
Keywords: aspects of consuption , wheat imortation , econometrie, price wheat, income Jel Classification Codes: C4.G5